Empowerment of Communities Creating Home Industry Business Based On Local Potential in Losari Village, Gondang District, Nganjuk Regency - S. Hidayat; A. Y. T Putra (Nusantara Science and Technology Proceedings)
Losari Village, Gondang District, is a village located in the northern part of Nganjuk Regency. The people of Losari Village are generally isolated from other villages in the Gondang sub-district because they are located in Perhutani's forests area. Economically, the people of Losari village are still poor. Most people work as farmers who can only grow crops in the rainy season. In an effort to increase family income, women have an important role in finding additional income, both in helping their husbands and in other activities that can increase income in an effort to improve family welfare. Therefore, the purpose of this Kuliah Kerja Nyata (KKN) was giving knowledge and skills to women in Losari village to create a home industry based on local potential commodity, especially corn. The survey was carried out using interview and questionnaire methods. The result is used to carry out focus groups discussion. The result of the agreed Focus Group Discussion (FGD) was the formation of joint business groups and corn crackers as the main products. The results of the FGD was formed the Kelompok Usaha Bersama Mekarsari (KUBE). Training activities for making corn crackers were carried out. In addition, accompaniment activities were carried out for product marketing